O Evangelho segundo a Pastoral da Criança :por uma pedagogia da sobrevivência - Nascimento, José Mateus do (2006)
This work aims to analyze social and educational actions at Pastoral da Criança, using education as a survival tool. This was done at Parque dos Coqueiros, a neighborhood in Natal, Rio Grande do Norte. The methodology for data collection was composed of comprehensive interview (Jean Kaufmann), participant observation (Robert Bogdan) and documental analysis (Le Goff); all os which bring reflections related to concepts such as strategies, tatics and know how (Michel de Certeau), configuration (Nobert Elias), and control technology (Michel de Foucault), care ethics (Leonardo Boff) and etno-theories (Natália Ramos). Pastoral da Criança is a social action organism that belongs to the National Conference of Bishops of Brazil, originated at Florestópolis, Londrina (Paraná), in the year of 1983. These actions have been an expression of a new logic of actions of the Catholic Church. It values the participation of laymen in the activities of the Pastoral. Thus, the parish is seen as a nucleus that irradiates the Church s Social Doctrine. At Rio Grande do Norte this institution has guided poverty stricken families on issues related to children s health as well as working with laymen for volunteer work. This is considered devotion, that is firmed by an individual and group mystique. The social and educational actions are done in three axes: 1) Monthly home visits, where there is mother-child support; 2) Life Celebration Day, where they weigh children and promote nutritional surveillance; 3) Meeting for Evaluation and Reflection, that aims to articulate community leaders to think about problems attached to the social actions they realize. This action tripod , as it is called by the Pastoral Agents are the types of actions that fundament survival education for poor children ranging from 0 to 6 years old. The families learn to deal with prevention, the essential, the alternative and probabilities of survival tactics due to exclusion matters or even social extermination. The Pastoral da Criança aims to recover childhood emotions in poverty stricken areas. It also has influence in the diminishing of malnutrition and mother and child mortality. This education for survival is the base on the art of teaching and learning of poverty stricken children. It is a social educational action, non assistencialist, but considered a shy action in order to promote mobilization of the communities that are accompanied for the emancipation and change of social conditions